2019
DOI: 10.26417/ejser.v6i3.p7-22
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Challenges of Integration in Swedish-speaking Ostrobothnia: Using the Structured Democratic Dialogue Process as a Tool

Abstract: The purpose of this study is to investigate ways to identify the challenges of integration of minority groups, such as migrants, ethnic/racial minorities, and refugees in Swedish-speaking Ostrobothnia by using the Structured Democratic Dialogue (SDD) as a participatory methodology. This particular method was selected for this study with the purpose to bring all identified stakeholders in the society together to collaboratively and collectively identify and further discuss the challenges and obstacles they face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…That is the reason why the action plans in these clusters did not take place on the influence map. Habes et al (2019) found that not including Finns in the integration process was one of the most influential challenges that hinders the integration process in Swedish-speaking Ostrobothnia. In order to overcome this challenge, the participants proposed 66 action plans categorized under eight clusters in order to include Finns in the integration process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is the reason why the action plans in these clusters did not take place on the influence map. Habes et al (2019) found that not including Finns in the integration process was one of the most influential challenges that hinders the integration process in Swedish-speaking Ostrobothnia. In order to overcome this challenge, the participants proposed 66 action plans categorized under eight clusters in order to include Finns in the integration process.…”
Section: Discussionmentioning
confidence: 99%
“…They found that although key factors such as citizenship, economy, education, housing, and rights are important, the social connection plays a vital role for a successful integration process at local level (Strang and Ager 2010). Habes et al (2019) identified "not including Finns in the integration process" as one of the most influential challenges hindering the successful integration process in Swedish-speaking Ostrobothnia. Thus, the focus of the current paper is to explore the action plans that could facilitate the inclusion of Finns in the integration process of minority groups in Swedish-speaking Ostrobothnia in order to overcome one of the most influential challenges of the integration process in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Habes et al (2019) found that negative attitudes toward minority groups, including the LGBTQ+ community, constitute one of the most significant obstacles to their integration in Swedish-speaking Ostrobothnia, Finland. As a result, the triggering question (TQ): "What actions (political, educational, financial, sociocultural, technological, etc.)…”
mentioning
confidence: 99%